1997
DOI: 10.1038/386457a0
|View full text |Cite
|
Sign up to set email alerts
|

Maximal sustained energy budgets in humans and animals

Abstract: Why are sustained energy budgets of humans and other vertebrates limited to not more than about seven times resting metabolic rate? The answer to this question has potential applications to growth rates, foraging ecology, biogeography, plant metabolism, burn patients and sports medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
445
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 467 publications
(461 citation statements)
references
References 37 publications
15
445
1
Order By: Relevance
“…Limits to SusEI are important because they affect all aspects of animal performance, including reproduction (Drent and Daan, 1980;Hammond and Diamond, 1997). Here, we showed that FI AS (=SusEI) and MEO during lactation were related between mothers and biological daughters, and this reflected genetic factors rather than maternal effects during lactation -although maternal effects during pregnancy could not be separated from genetic effects using our protocols.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Limits to SusEI are important because they affect all aspects of animal performance, including reproduction (Drent and Daan, 1980;Hammond and Diamond, 1997). Here, we showed that FI AS (=SusEI) and MEO during lactation were related between mothers and biological daughters, and this reflected genetic factors rather than maternal effects during lactation -although maternal effects during pregnancy could not be separated from genetic effects using our protocols.…”
Section: Discussionmentioning
confidence: 65%
“…adipose tissue) (Drent and Daan, 1980;Peterson et al, 1990;Weiner, 1992). SusEI is an important parameter because it may provide an upper bound that constrains many aspects of animal performance, like reproductive output, migration behaviour and thermoregulatory capabilities (Drent and Daan, 1980;Hammond and Diamond, 1997;Johnson et al, 2001a;Piersma, 2011;Speakman and Król, 2005a). To date, much research has focused on finding the factors that might impose intrinsic physiological limits on maximum SusEI.…”
Section: Introductionmentioning
confidence: 99%
“…SusMR is presumed to be limited by an animal's morphology. A big gut, and associated organs (such as the liver) that can process energy faster, makes more energy available to support SusMR but also requires a greater amount of maintenance (BMR) (Drent and Daan, 1980;Hammond and Diamond, 1992;Hammond and Diamond, 1997;Peterson et al, 1990;Weiner, 1989;Weiner, 1992). Therefore, an individual with a higher BMR will have greater capacity for SusMR and, if available energy is unlimited, they may be able to sustain greater reproductive output.…”
Section: Introductionmentioning
confidence: 99%
“…Cold-blooded reptiles (ϳ10 4 ) have ⌽ m values higher than globally averaged plants (ϳ10 3 ), warm-blooded mammals typically more (ϳ5 ϫ 10 4 ); examining animal life with finer scale, sedentary humans (ϳ2 ϫ 10 4 ) have less ⌽ m than for laboring humans (ϳ6 ϫ 10 4 ), which, in turn, have less than bicycling humans (ϳ10 5 ), and so on [20]. Starting with life's precursor molecules (the realm of chemical evolution) and all the way up to human brains exemplifying the most complex clump of matter known (neurological evolution), the same general trend characterizes plants and animals as for stars and planets: The greater the apparent complexity of the system, the greater the flow of free energy density through that system-either to build it, or to maintain it, or both.…”
Section: Figurementioning
confidence: 99%